2021
DOI: 10.1136/lupus-2021-000522
|View full text |Cite
|
Sign up to set email alerts
|

Safety of procuring research tissue during a clinically indicated kidney biopsy from patients with lupus: data from the Accelerating Medicines Partnership RA/SLE Network

Abstract: ObjectivesIn lupus nephritis the pathological diagnosis from tissue retrieved during kidney biopsy drives treatment and management. Despite recent approval of new drugs, complete remission rates remain well under aspirational levels, necessitating identification of new therapeutic targets by greater dissection of the pathways to tissue inflammation and injury. This study assessed the safety of kidney biopsies in patients with SLE enrolled in the Accelerating Medicines Partnership, a consortium formed to molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
2
1

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Twenty biopsy specimens obtained in the first 2 years of follow-up included three showing class II lupus nephritis, three with class III, seven with class IV, three with class V, two with class III/V, and one with class VI lupus nephritis; one biopsy was performed at an outside hospital and was not available (although this patient was started on immunosuppression on the basis of the biopsy result). Progressors who underwent a biopsy were younger compared with progressors who did not undergo a biopsy: median (IQR) age of 25 (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39) and 36 (28-50) years old, respectively (P50.007).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty biopsy specimens obtained in the first 2 years of follow-up included three showing class II lupus nephritis, three with class III, seven with class IV, three with class V, two with class III/V, and one with class VI lupus nephritis; one biopsy was performed at an outside hospital and was not available (although this patient was started on immunosuppression on the basis of the biopsy result). Progressors who underwent a biopsy were younger compared with progressors who did not undergo a biopsy: median (IQR) age of 25 (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39) and 36 (28-50) years old, respectively (P50.007).…”
Section: Resultsmentioning
confidence: 99%
“…The logical extension in considering the clinical implications of low-grade proteinuria would be to obtain a kidney biopsy at these lower thresholds for these patients at higher risk. Therefore, invoking the safety of kidney biopsy is relevant: recent published data from the Accelerating Medicines Partnership (AMP) showed 34 of 475 (7%) patients with SLE, who were followed prospectively for safety, experienced a related adverse event from a kidney biopsy, with 18 (4%) events deemed serious enough to require hospitalization (26). Comparatively, despite additional research tissue being obtained, patients in AMP had fewer adverse events than reported in the historical cohorts and meta-analyses of patients undergoing clinically indicated biopsies (27,28).…”
Section: Discussionmentioning
confidence: 99%
“…This work indicates a valuable role for blood cellular biomarkers in evaluating specific dimensions of immune activity of patients with LN to gain insight into the likelihood of response to standard immunosuppressive LN therapies. Phase II study (37,82) if 1) they fulfilled American College of Rheumatology (83) or Systemic Lupus International Collaborating Clinics classification criteria (84) for SLE, 2) had a clinically-indicated renal biopsy for a UPCR > 0.5 (16,17) and 3) had biopsy-confirmed lupus nephritis of class III, IV and/or V, based on the International Society of Nephrology/Renal Pathology Society (ISN/RPS) (15). Patients with a history of renal transplantation, with a medical condition considered at risk of participating in this study by the investigator, who was pregnant at the time of study entry, or who had recently been exposed to rituximab (within the past six months) were excluded.…”
Section: Discussionmentioning
confidence: 99%
“…Systemic lupus erythematosus (SLE) affects >200,000 Americans, of whom >40% will develop lupus nephritis and 8-10% will develop renal failure over 20 years (1) (2) (3). SLE is caused by the loss of immune tolerance and the production of autoantibodies against nuclear material.…”
Section: Introductionmentioning
confidence: 99%